Ginsenoside Rg3 ameliorated HFD-induced hepatic steatosis through downregulation of STAT5-PPARγ. Issue 3 (December 2017) - Lee, Jin-Bong; Yoon, Sung-Jin; Lee, Sang-Hyun; Lee, Moo-Seung; Jung, Haiyoung; Kim, Tae-Don; Yoon, Suk Ran; Choi, Inpyo; Kim, Ik-Soo; Chung, Su Wol; Lee, Hee Gu; Min, Jeong-Ki; et al.
Abstract : Healthy expansion of adipose tissue maintains metabolic homeostasis by storing excess chemical energy in increased fat mass. The STAT5-PPAR gamma pathway reportedly regulates adipocyte differentiation, lipid metabolism and adipogenesis. Ginsenoside Rg3 is one of the diverse groups of steroidal saponins, the major active components of ginseng, which have demonstrated pharmacological properties. In this study, we evaluated the therapeutic effects of ginsenoside Rg3 under pathological conditions in vitro and in vivo . We examined the effects of ginsenoside Rg3 on glucose level, insulin sensitivity and lipogenesis in high-fat diet-fed C57BL/6 mice. Ginsenoside Rg3 was also applied to the pre-adipocyte cell line 3T3-L1 to assess the impact on lipogenesis. Ginsenoside Rg3 reduced epididymal white adipose tissue (eWAT) size and hepatic steatosis, and the amount of triglycerides (TGs) in both eWAT and liver. Similar to the murine model, Rg3-treated 3T3-L1 cells showed a reduction in lipid accumulation and amount of total TGs. Ginsenoside Rg3 regulates the expression of PPAR gamma though STAT5 in vitro and in vivo . According to our results, lipid metabolism-related genes were downregulated in the high-fat mice and 3T3-L1 cell line. Rg3 shows potential for the amelioration of obesity-induced pathology, acting though STAT5-PPAR gamma to facilitate the healthy functioning of adipose tissue. This is the first report of evidence that obesity-induced insulin resistance and lipotoxicity can be treated with ginsenoside Rg3, which acts though the STAT5-PPAR gamma pathway in vivo and in vitro .